2012
DOI: 10.1080/22311866.2012.10719121
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic and Flavonoids Content, Antioxidant and Antimicrobial Activities ofAzilia eryngioidesExtracts

Abstract: The aim of this research was to assay the phenolic and flavonoid content of ethanolic, methanolic and water extracts of Azilia eryngioides and its related antimicrobial and antioxidant activity. Total phenolic, flavonoid content, DPPH radical scavenging activity and beta carotene linoleic acid of extracts were spectrophotometrically determined. The antimicrobial activity was determined by micro broth dilution assay. The total phenolic content was measured in highest amount in Azilia eryngioides ethanolic (79.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…has also been reported [11][12][13][14]. Contrasting results are reported in literature regarding the effect of flavonoids on antifungal activity.…”
contrasting
confidence: 40%
“…has also been reported [11][12][13][14]. Contrasting results are reported in literature regarding the effect of flavonoids on antifungal activity.…”
contrasting
confidence: 40%
“…There are a positive correlation between total phenolic and flavonoid contents and the antioxidant and antimicrobial activities. The positive correlation between total phenolic and flavonoid contents and the antioxidant effects were observed for Azilia eryngioides ethanol extract (13), while this correlation was reverse for Sambucus nigra extracts (14). Therefore, the direct correlation between total phenolic content of extract and its antioxidant activity is not an absolute relation.…”
Section: Discussionmentioning
confidence: 97%
“…showed more sensitivity to P. spinosa extracts, especially to its ethanol extract. A higher total phenolic content and consequently, a higher antimicrobial activity against fungi was detected for A. eryngioides (13), while P. spinosa ethanol extract showed less activity against Gram-negative bacteria and fungi. Therefore, different phenolic compounds target different functions of microbial cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that reported a direct relation between their antioxidant and antimicrobial activities and TFC and TPC 14,15 , also is reported a negative relation between TPC, TFC and antioxidant activity 16 .…”
Section: Antimicrobial Evaluationsmentioning
confidence: 95%